Caring for an older person with dementia in the Emergency Department (ED): An Appreciative Inquiry exploring family member and ED nurse experiences. Issue 15 (24th April 2019) - Watkins, Sarah; Murphy, Fiona; Kennedy, Catriona; Dewar, Belinda; Graham, Margaret
Abstract: Aims and objectives: To generate insights about what matters and is valued by family members of older people with dementia in the emergency department. To explore the experiences of emergency nurses looking after older people with dementia in an episode of care. Background: In the emergency department, older people with dementia are at risk of suboptimal care. Little is known of the experiences of family members of being with an older person with dementia in the emergency department or the experiences of emergency nurses looking after older people with dementia in this environment. Design and methods: Phase 1 Data Analysis of the Discovery Phase of an Appreciative Inquiry study. Study participants were family members of older people with dementia and emergency nurses. Data collection methods included interviews with family members of older people with dementia and 30 hr of participant observation working alongside emergency nurses. This study was guided by the Standards for Reporting Qualitative Research. Results: Two themes emerged from the analysis: What matters to family members with four subthemes and challenges for family members and nurses in the emergency department with two subthemes. Conclusion: This study demonstrates that some emergency nurses are connecting with family members even in the briefest of clinical encounters. It is feasible for more emergency nurses to do the same more of the time. Relevance to clinical practice: The older person with dementia must be given a triage category of no less than 3 (to be seen by the doctor within the hour) on arrival in the department. Further education is needed to assist emergency nurses to establish rapport and incorporate family member insights as part of care planning and assessment of the needs of the older person with dementia.